Competence Profiles of Vocational Teachers in Sweden - Sofia Antera; Staffan Nilsson (International Journal for Research in Vocational Education and Training, 2025)
Context: Vocational teachers’ professional work builds on both vocational and teaching competence, requiring vocational teachers to balance multiple identities in their professional practice. As a professional group coming to education from different vocational disciplines, vocational teachers also have various educational backgrounds, teaching experience, or competence profiles. Nevertheless, teacher training programmes treat them as a homogeneous group. This study aims to identify competence profiles among vocational teachers in Sweden and analyse background factors associated with these competence profiles.